Pembiayaan Modal Usaha Melalui Akad Ijarah Di KSPPS Ankasa Karangdowo, Kedungwuni, Kabupaten Pekalongan: Pembiayaan Modal Usaha Melalui Akad Ijarah Di KSPPS Ankasa Karangdowo, Kedungwuni, Kabupaten Pekalongan - Irma Yuli Ana; Heris Suhendar; Iqbal Kamalludin (Fakultas Syariah Universitas Islam Negeri (UIN) K.H. Abdurrahman Wahid Pekalongan, 2021)
KSPPS (Sharia Savings and Loans and Financing Cooperative) is an independent business unit in which it develops productive businesses to improve the economic quality of small entrepreneurs by encouraging saving activities, and supporting the financing of economic activities. The financing contracts used include mudharabah, musyarakah, murabahah and ijarah. One of the contract products at KSPPS Ankasa which is in great demand by the public is ijarah. This research is an empirical juridical research using a qualitative approach which aims to analyze the fatwa of DSN No. 09/DSN-MUI/IV/2000 on the practice of financing venture capital through an ijarah agreement at KSPPS Ankasa Karangdowo, and to explain the legal consequences of the practice of financing business capital through an ijarah agreement at KSPPS Ankasa Karangdowo.The results showed that the application of the ijarah contract at KSPPS Ankasa, namely when viewed from Islamic law refers to the DSN Fatwa No. 09/DSN-MUI/IV/2000 is not in accordance with the terms of the pillars and terms of the ijarah because there is no object of ijarah. KSPPS as a lessor does not provide goods, but only provides funds that cannot be taken advantage of except by spending. Meanwhile, if you look at the system from ujrah, KSPPS Ankasa uses a profit-sharing system, not the ujrah system. This is not in accordance with the DSN Fatwa No. 09/DSN-MUI/IV/2000 that the ijarah contract does not use profit sharing but ujrah/fee in exchange for the benefits received by the customer.